The electrostatic field networking in three isolated thunderstorms - Zhenhui Wang; Qingfeng Zeng; Fengxia Guo; Dongpu Xu; Hao Wang (Institute of Advanced Engineering and Science, 2013)
A method for networking atmospheric electrostatic field by a quasi-normal charge distribution model based on radar and sounding data in isolated storm cells has been proposed. The charge distribution parameters of thundercloud are first estimated and inversed, and then the network of atmospheric electrostatic field can be calculated with the obtained parameters. The method was used to analyze three isolated thunderstorms that passed through the experiment site in 2009. It was shown that the electrostatic field networking and the charge distribution were concordant with the location of lightning and radar echo. It is revealed that the model and obtained parameters are reasonable to some extent and the method for networking electrostatic field using radar and sounding data is feasible. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1871